A Case of Subglottic Granuloma Requiring an External Cervical Incision - Sasawaki, Mayuko; Yamaguchi, Wataru (JIBI INKOKA TEMBO, 2023)
Laryngeal granulomas are considered to be caused by general anesthesia, emergency airway management, endotracheal intubation for the purpose of respiratory management of chronic illness, trauma, and infection. In particular, subglottic granuloma is a relatively rare disease that tends to recur and is often difficult to treat. Herein, we report a case of subglottic granuloma that developed after long-term intubation and was successfully treated surgically. The patient, a 32-year-old Indian male, had COVID-19 pneumonia and was treated with long-term tracheal intubation at another hospital. At the initial visit, wheezing on inhalation was observed, and bilateral vocal cord immobility was observed on the laryngeal fibers, which led to the suspicion of bilateral vocal cord paralysis. An emergency tracheotomy was performed on the same day, and when the subglottis was checked through the tracheostomy, a huge subglottic granuloma was found in the posterior part of the glottis. The subglottic granuloma was in contact with the back surface of the bilateral vocal cords and was considered to be the cause of the glottal opening defect. After tracheotomy and conservative treatment for 2 weeks, the size of the subglottic granuloma did not change. Therefore, we planned to remove the subglottic granuloma through an external cervical incision. Under general anesthesia, the subglottic granuloma was removed through a cricothyrotomy with a rigid endoscope. The glottis was opened postoperatively, and the tracheal cannula was removed 2 months after surgery. Nine months have passed since surgery, and laryngeal fiberoptic findings have not revealed any recurrence.